Understanding Moral Values in the Memoir Entitled Educated by Tara Westover - Desak Putu Eka Pratiwi; I Gusti Agung Sri Rwa Jayantini; I Putu Ade Pratama (English Department, Faculty of Humanities, Udayana University, 2023)
This article is focused on how to analyse any moral values portrayed in the memoir